Prevalence of enteropathogens in normal feces from healthy children at an infant day care in Brazil - Cláudia Moura; Maria Clara Duarte Fregolente; Isabel Julien Martini; Daniela Ferreira Domingos; Erivaldo José da Silva; Mirtis Maria Giaciani Ferraz; Maria Silvia Viccari Gatti; Domingos da Silva Leite (Journal of Infection in Developing Countries, 2012)
Introduction: The diarrhea associated with gastroenteritis is a major cause of morbidity and mortality worldwide, affecting mainly infants. The characterization of both viral and bacterial agents associated with gastroenteritis can establish policies for surveillance, prevention and treatment of infections. Group A rotaviruses are the major infectious agent associated with dehydration in children, followed by pathotypes of Escherichia coli. There are three main types of clinical infections caused by E. coli strains that have acquired virulence genes: (i) enteric and diarrheal diseases, (ii) urinary tract infections, and (iii) sepsis and meningitis.